Effects of Ionized Water on Certain Egg Quality Traits and the Levels of Proteins and Enzymes in the Blood of the Japanese Quail Coturnix japonica - Ezzat, Hasanain N.; Shihab , Ihsan M.; Hussein, Mohammad A. (International Journal of Poultry Science, 2017)
Objective: This experiment was conducted to study the effects of ionized water on certain egg quality traits and the levels of proteins and enzymes in the blood of the Japanese quail Coturnix japonica . Materials and Methods: One hundred 42-day-old quail were randomly distributed among five treatment groups with four replicates for each group. The following treatments were used: T1 (control): The birds were provided normal water, T2: The birds were provided alkaline water (pH = 8), T3: The birds were provided alkaline water (pH = 9), T4: The birds were provided acidic water (pH = 6) and T5: The birds were provided acidic water (pH = 5). A Complete Randomized Design (CRD) was used to investigate the effects of the studied treatments on different traits. Results: Significant (p<0.05) differences in the total mean length and width of the egg and shell thickness were observed between treatments, T2 and T4 surpassed the other treated groups in egg length, at values of 32.12 and 32.27 mm, respectively. However, T2 and T3 produced the greatest egg widths, which were 25.44 and 25.38 mm, respectively. However, T2 produced the highest mean shell thickness of 0.25 mm. On the other hand, T3 produced the highest blood protein levels compared with the other treated groups, whereas T1 produced the highest blood enzyme levels in this study. A pH of 8 or 9 in drinking water resulted in the best egg quality traits and protein and enzyme levels in the blood. Alkaline and acidic water may provide an effective, safe, non-toxic and relatively inexpensive treatment to produce the best egg quality traits and protein and enzyme levels. Conclusion: The inclusion of alkaline and acidic water has beneficial effects on Japanese quail production and may be considered a low-cost option to improve general production parameters.